Studies in arts and sciences : a felicitation volume to Arunkalaikkon Prof. N. Subbu Reddiar, Ph.D. in commemoration of his sixty-first birth-day - Thiruvenkatachari, S. (Ram Bros : available from SISSWP Society, 1978)
Contributed articles.